Effects of Mental Fatigue in Total Running Distance and Tactical Behavior During Small-Sided Games: A Systematic Review With a Meta-Analysis in Youth and Young Adult's Soccer Players - Clemente, Filipe Manuel; Ramirez-Campillo, Rodrigo; Castillo, Daniel; Raya-González, Javier; Silva, Ana Filipa; Afonso, José; Sarmento, Hugo; Rosemann, Thomas; Knechtle, Beat (Frontiers in Psychology, 2021)
Background: Mental fatigue can impact physical demands and tactical behavior in sport-related contexts. Small-sided games (SSGs) are often used to develop a specific sport-related context. However, the effects of mental fatigue on physical demands and tactical behaviors during soccer SSGs have not been aggregated for systematical assessment. Objective: This systematic review (with a meta-analysis) was conducted to compare the effects of mental fatigue vs. control conditions in terms of the total running distance and tactical behavior of soccer players during SSGs. Methods: The data sources utilized were PubMed, PsycINFO, Scielo, Scopus, SPORTDiscus, and Web of Science. The study eligibility criteria were established based on PICOS: (i) Population: healthy youth and young adult men soccer players with regular training practice and belonging to teams with regular competitions; (ii) Intervention: exposed to mental fatigue-induced protocols only before SSGs; (iii) Comparator: control conditions (passive or active not promoting mental fatigue) before SSGs; (iv) Outcomes: physical demands (total running distance) and tactical behavior (attacking behavior accuracy, pass decision-making accuracy, and space exploration index); (v) Study design: counterbalanced cross-over design; and (vi) only full-text and original articles written in English. Results: The database search initially identified 111 titles. From those, six articles were eligible for the systematic review and meta-analysis. Results showed no significant effect of fatigue on total running distance (ES = 0.13; p = 0.307) and tactical behaviour (ES = 0.56; p = 0.079). Conclusions: A non-significant effect of mental fatigue on total running distance and tactical behaviors performed by soccer players during SSGs was found in this systematic review.